Towards an assessment of fresh expressions of Church in ACSA (the Anglican Church of Southern Africa) through an ethnographic study of the community supper at St Peter's Church Mowbray, Cape Town - Aldous, Benjamin James (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhD)--Stellenbosch University, 2019.